Recent personal income tax progressivity trends in Australia - Graeme Davis; Philip Akroyd; David Pearl; Tristram Sainsbury (The Australian Government, The Treasury, 2019)
Tax progressivity is not a precise science. Judgements around the level of tax progressivity need to balance the objective of fairness against other objectives - such as efficiency, simplicity and sustainability - that underpin the design of tax systems. Further, people's perceptions of fairness depend on a range of factors, including their position in society and the information available to assess their position relative to others. Our analysis of average personal income tax rates, and the distribution of personal income tax incidence, over recent decades suggests that Australia's personal income tax system became more progressive over the 22 years between 1994-95 and 2015-16. Choices by successive Australian governments have altered marginal personal income tax rates and extended tax thresholds in ways that have reduced the income tax incidence on lower income earners, and increased the income tax incidence on higher income earners. This has also seen an increase in income tax concentration, whereby a narrower proportion of high income earners pay a larger share of total Australian personal income taxes. In publishing these findings, we seek to inform the trade-offs arising from the progressive personal income tax regime and its role within the broader Australian tax system. However, care needs to be taken in evaluating these findings. Our analysis does not seek to evaluate the fairness (real or perceived) of Australia's personal income tax.
Keywords: 330